Does the salt really matter? Impact of the counterion upon ECL signal. (10th March 2021) - Brown, Kelly; Gillies, Christina; Allan, Pamela; Dennany, Lynn
Abstract: The incorporation of counterions into a variety of substances to control a number of their physiochemical properties is vital within a range of fields. Electrochemiluminescence (ECL) based sensors have grown in popularity in recent years with their employment observed across analytical and bioanalytical applications. ECL is typically concerned with the core electroactive functionality of the species of interest, with structural similarities commonly employed to determine the likelihood of a species ECL capability. However, to date no consideration has been given to the impact of different counterions toward an analytes ECL mechanism. Here we report for the first time how a simple alternation to a co-reactants counterion can significantly impact upon its recorded ECL response. Utilizing the tropane alkaloid scopolamine and its hydrobromide and hydrochloride salt forms, we have seen through interrogation with the traditional ruthenium luminophore, that replacement of the bromide anion for the chloride anion can reduce the electroactivity of the species. Direct comparison between the hydrobromide and hydrochloride salt forms relived differences in respect of their emission potentials and intensities. The impact of the salt form upon the ECL response has here been investigated, in respect to predicted concentrations. Results demonstrated how vastly different concentrations were obtained dependent upon the salt form present within the sample and that which was used to produce the calibration curve. The impact of this discovery will be of interest to the electrochemiluminescent and electroanalytical communities, and in particular forensic practitioners where electrochemical and ECL based sensors are of increasing interest. Ultimately the application of an ECL sensor within an analytical environment relies upon its accuracy and hence a thorough understanding of the phenomenon observed will only stand to widen the acceptance of ECL within the wider analytical community and increase its potential future applications.